Relapsing Polychondritis with Tracheobronchial Involvement: A Detailed Description of Two Pediatric Cases and Review of the Literature - Winter, Greta; Löffelmann, Tara; Chaya, Shaakira; Kaiser, Hannah; Prenzler, Nils Kristian; Warnecke, Athanasia; Wetzke, Martin; Derlin, Thorsten; Renz, Diane; Stueber, Thomas; Länger, Florian; Schütz, Katharina; Schwerk, Nicolaus (Klinische Pädiatrie, 2024)
Relapsing polychondritis (RP) is a rare immune-mediated disease that primarily affects the cartilaginous structures of the ears, nose and airways. The clinical spectrum ranges from mild to severe disease characterized by progressive destruction of cartilage in the tracheobronchial tree leading to airway obstruction and acute respiratory failure. Early diagnosis is crucial to prevent irreversible airway damage and life-threatening complications. Due to its rarity and variability of symptoms, the diagnosis of RP is often delayed particularly in childhood. To address this and increase awareness of this rare disease, we present a detailed case report of two adolescent females affected by RP. We aim to describe the clinical findings, consequences of a delayed diagnosis and provide a review of the current literature.
Keywords: Relapsing Polychondritis; airways; childhood; adolescents; bronchial stenosis